Sorte moral e epistêmica: uma investigação sobre possíveis aproximações entre os dois fenômenos - Rosauro, João Victor Nunes (Universidade do Vale do Rio dos Sinos, 2022)
The aim of this dissertation is to investigate how the phenomenon of moral luck can be better understood from its possible relationships with epistemic luck. At first, what unites the two phenomena is the fact that luck factors influence the moral and epistemic credit we attribute to agents for their moral behavior and cognitive acquisitions. However, knowing that the epistemic phenomenon in question has its formal birth prior to the problem of moral luck, it is valid to ask whether both fields of debate manage to trace deeper similarities in the two cases. The validity of this question is based on a common interest in the areas, that is, that in order to attribute censorship and moral praise, as well as to attribute knowledge to someone, we must exclude factors of luck, as they seem to detract from the agency's merit. Thus, by investigating these connections of moral luck with its epistemic counterpart, we can delve deeper into new dimensions of the problem, as well as outline possible solutions that aim to defend the relevance of the moral phenomenon in question. That said, the work approaches authors such as John Greco, Linda Zagzebski, Robert Hartman and Duncan Pritchard, who offer analyzes of the approximations of phenomena based on skepticism, symmetries between moral and epistemic discourse, the possibility of moral and epistemic agency in the face of elements luck, and classification categories that are analogous to both phenomena. In extension, it will also be seen that a common point between these authors is the proposal of virtue ethics, as well as the epistemology of virtues, to reconcile the merit of moral and epistemic agency and luck factors. Having established the objective, I will proceed to the characterization of the problem.
Keywords: Sorte moral; Sorte epistêmica; Moral luck; Epistemic luck; ACCNPQ::Ciências Humanas::Filosofia